Uncertainty and modelling cost based methodology for modelling choices in multiscale structures. Issue 1 (2022) - Pila, E.C.Rodriguez; Guillebaud, C.; Wargnier, H.; Perry, N.
Abstract: Choices made in the design phases of multiscale structures are guided by the integration of knowledge on parameters at different scales of observation of the structure. These choices are often based on many experimental and predictive campaigns which increase modelling costs. The work developed here integrates the consideration of uncertainties in order to rationalise the cost of modelling (predictive and experimental) while controlling uncertainty over those parameters that are of interest for the structure scale. The methodology is applied to the study of a thick composite pressure vessel to be used for hydrogen storage.